Effects of social and physical factors on native forest degradation - Vergara, Gerardo; Gayoso, Jorge (Bosque (Valdivia), 2004)
The environmental impact on the native forests of the Province of Valdivia by access roads and populations was analyzed in this study. In agreement with other studies, the most significant impact on the forest occurred within a strip of 3 km on each side of the road, where the rate of deforestation was between 22% and 51%. A model comprising physical and social factors explained the driving forces of forest degradation. Some biophysical variables and a high percentage of rural populations explained most of the intervention in the forest. A Principal Component Analysis proved an adequate technique for evaluating the importance of factors and their relationship with the spatial component.